2021
DOI: 10.1177/03000605211018448
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation and suboptimal treatment of breast cancer among Syrian refugees: a retrospective study

Abstract: Objectives The crisis in Syria has had a profound impact on the entire region. In this study, we report the patterns of presentation and management of Syrian patients with breast cancer treated at our institution. Methods We retrospectively collected data on Syrian refugees treated for breast cancer over the past 10 years at our center. Management was compared against our approved clinical practice guidelines. Results A total of 113 patients were eligible and included. The median age (range) at diagnosis was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…12,13 There are little data on diagnostic delays in Syria; however, a study among Syrian refugees in Jordan noted that 65% presented with metastatic disease and as a result received delayed and suboptimal treatment. 14 A study from Konya province in Turkey reported on 230 adult and 38 children who are Syrian refugees diagnosed with cancer between 2005 and 2020. 15 They noted that 40% of patients had metastatic cancer at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 There are little data on diagnostic delays in Syria; however, a study among Syrian refugees in Jordan noted that 65% presented with metastatic disease and as a result received delayed and suboptimal treatment. 14 A study from Konya province in Turkey reported on 230 adult and 38 children who are Syrian refugees diagnosed with cancer between 2005 and 2020. 15 They noted that 40% of patients had metastatic cancer at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exclusively studying the Syrian populations in Turkey reported that the majority of Syrian refugees present with breast cancer and advanced stages. On the other hand, Jordanian reports showed a dominance of localized breast cancer cases among Syrian refugees (10,42,43). The UNHCR demonstrated that, in general, refugees in formal camps have very poor survival outcomes even when diagnosed early with cancer.…”
Section: Figurementioning
confidence: 99%
“…In addition, they are more likely to present with advanced stages and suffer more complications because of poor hygiene and living conditions, as well as limited access to care and resources available (8). For refugees, host countries encounter serious challenges in health provision to cancer patients considering the economic pressures they face and the lack of infrastructure, all of which lead to suboptimal care delivery to this subset of patients (9,10). Furthermore, the course of treating many types of cancer requires a robust healthcare system with the ability to provide effective screening programs, diagnostic services, and treatment modalities (e.g., surgery, radiotherapy, or chemotherapy) (11).…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of Syrian refugees who reside within host communities in Jordan have access to public health services, including breast cancer screening. Healthcare costs for Syrian refugees are comparable to those of uninsured Jordanians [ 12 ]. On the other hand, refugees living in camps have free access to healthcare services provided by the Jordanian government and international refugee assistance agencies, which tend to be in most cases suboptimal [ 13 ].…”
Section: Introductionmentioning
confidence: 99%